Optimal configuration of active and backup servers for augmented reality cooperative games. (24th March 2018) - Bujari, Armir; De Giovanni, Luigi; Palazzi, Claudio E.
Summary: Interactive applications as online games and mobile devices have grown in popularity. From their combination, new and interesting cooperative services could be generated. For instance, gamers endowed with Augmented Reality (AR) visors, connected as wireless nodes in an ad‐hoc network, can interact with each other while immersed in the game. To enable this vision, we discuss here a hybrid architecture enabling game play in ad‐hoc mode instead of the traditional client‐server setting. In our architecture, one of the player nodes also acts as the server of the game, whereas other backup server nodes are ready to become active servers in case of network disconnection, ie, due to low energy level of the currently active server. This allows to have a longer gaming session before a disconnection occurs due to energy exhaustion. In this context, the server election strategy with the aim of maximizing network lifetime is not so straightforward. To this end, we have analyzed this issue through a Mixed Integer Linear Programming (MILP) model considering static network topologies and both numerical and simulation‐based analysis shows that the backup servers solution fulfills its design objective. Contemplating for mobility, we present a simulation study employing actual packet routing protocols and discuss the tradeoffs that emerge.